Implementasi Metode Amazing Iqro dalam Pembelajaran Membaca Al-Qur'an - Amar; Surana, Dedih; Sobarna, Ayi (UNISBA Press, 2024)
Abstract. The objectives of this research are: (1) To identify the data on the planning of Quran learning and describe the Quran reading instruction through the Amazing Iqro method at SD Sains Al-Biruni Bandung. (2) To identify the data on the process of Quran learning and describe the Quran reading instruction through the Amazing Iqro method at SD Sains Al-Biruni Bandung. (3) To identify the methods used in Quran reading at SD Al-Biruni Bandung using the Amazing Iqro method. (4) To identify the strengths and weaknesses of Quran learning through the Amazing Iqro method. (5) To identify the supporting and inhibiting factors in Quran reading instruction using the Amazing Iqro method. The research findings indicate that: (1) The planning of Quran reading instruction using the Amazing Iqro method for grades 1 to 3 at SD Sains Al-Biruni Bandung is structured and aligned with the established targets of Amazing and the school. (2) The implementation process of Quran reading instruction using the Amazing Iqro method is running quite well in accordance with the planning. (3) The Amazing Iqro method in the Quran reading instruction process conducted by students at SD Sains Al-Biruni Bandung has had a significant effect on the students. (4) The strength of the Amazing Iqro method is that it facilitates Quran reading instruction, while its weaknesses are continually being addressed by the Amazing Academy team. (5) The supporting and inhibiting factors that arise in this issue are being effectively managed by the Quran teachers / Amazing team. Abstrak. Tujuan penelitian ini adalah untuk (1) Mengetahui data-data perencanaan pembelajaran Al Qur’an & mendeskripsikan pembelajaran membaca Al-Quran melalui metode Amazing Iqro di SD Sains Al-Biruni Bandung. (2) Mengetahui data-data proses pembelajaran Al Qur’an & mendeskripsikan pembelajaran membaca Al-Quran melalui metode Amazing Iqro di SD Sains Al-Biruni Bandung. (3) Mengetahui metode yang digunakan dalam membaca Al-Quran di SD Al-Biruni Bandung menggunakan Amazing Iqro. (4) Mengetahui keunggulan dan kelemahan pembelajaran Al-Quran melalui metode Amazing Iqro. (5) Mengetahui factor pendukung dan factor penghambat pembelajaran membaca Al-Quran menggunakan metode Amazing Iqro.. Hasil penelitian menunjukkan bahwa: : (1) Perencanaan pembelajaran membaca Al-Quran menggunakan metode Amazing Iqro kelas 1 sampai kelas 3 SD Sanis Al-Biruni Bandung ini dilakukan dengan terstruktur sesuai dengan rencana yang sudah di tetapkan pada target Amazing dan pihak sekolah. (2) Proses pelaksanaan pembelajaran membaca Al-Quran menggunakan metode Amazing Iqro berjalan cukup baik sesuai dengan perencanaan. (3) Metode Amazing Iqro dalam proses pembelajaran membaca Al-Quran yang dilakukan peserta didik di SD Sains AlBiruni Kota Bandung memberikan efek yang signifikan terhadap peserta didik. (4) keunggulan dari metode Amazing Iqro dapat memudahkan dalam pembelajaran membaca Al-Quran, sedangkan kelemahan metode Amazing Iqro akan terus diperbaiki oleh tim Amazing Academy. (5) Faktor pendukung dan penghambat yang muncul terhadap permasalahan ini dapat teratasi dengan cukup baik oleh para guru Quran / Tim Amazing.